Board members' educational background and financial performance: Evidence from Eurozone banks - Vítor Manuel Morais Pereira; José António Filipe (Journal of Central Banking Theory and Practice, 2022)
This study examines the impact of the quality of board members' educational background on the financial performance of a group of Eurozone banks. Return on average assets (ROAA), Return on average equity (ROAE), and Tobin's Q are used as measures to assess bank financial performance. Three indices are used as proxies for board members' educational qualifications: Eduindex, for all academic qualifications in areas such as business or economics; Eduversal, for all qualifications from business schools ranked by Eduniversal; and EduFT, for all qualifications from business schools ranked by the Financial Times. Our study results offer relevant policy implications. Generally, there is a significant negative effect from Eduversal and EduFT qualifications on bank financial performance. This effect can be explained by the fact that some well-qualified board members use their expertise for their own interest, which, in most cases, is not favourable for bank financial performance. The implication is that the European Central Bank needs to implement more rigorous measures than those currently imposed to control bank board member behaviour and reduce agency problems.
Keywords: C10; G20; 330; Bank financial performance; corporate governance; board of directors; educational background; Eurozone banking